Physiotherapeutic intervention in spinal muscular amyotrophy type 1: literature review (Research, Society and Development, 2021)
Spinal Muscular Amyotrophy (SMA) is a genetic disorder of autosomal recessive, degenerative neuromuscular inheritance. It mainly affects the motor neurons of the anterior horn of the spinal cord. According to the age of onset of clinical manifestations and motor impairment, EBF is classified into four types (I to IV). This literary review study aims to expose the etiology, pathophysiology, diagnosis, treatment and the importance of physical therapy intervention in patients with Spinal Muscular Amyotrophy, specifically in type I SMA. In this research, articles that were considered for inclusion criterious involved the theme with regard to physical therapy intervention in Spinal Muscular Amyotrophy type 1. The publication of the data collected took place between 2007 and 2021, in Portuguese, English and Spanish. The bibliographical survey was carried out in the following databases: Scielo, Pubmed, PEDro, Lilacs and Academic Google, from March to October. During the research, physiotherapeutic intervention was observed in Spinal Muscular Amyotrophy, specifically in type 1 SMA. Concluding that the mode of action of physiotherapy advocates minimizing/slowing down the clinical manifestations that affect the musculoskeletal system and complications in the respiratory system, contributing to promote quality and prolong life, and consequently preventing the death of these patients.